Hepatitis B Virus Genotype-Dependent Vulnerability of Infected Cells to Immune Reaction in the Early Phase of Infection - Shiina, Masaaki; Yamada, Norie; Sugiyama, Ryuichi; Murayama, Asako; Aly, Hussein Hassan; Muramatsu, Masamichi; Wakita, Takaji; Imawari, Michio; Kato, Takanobu (Frontiers in Microbiology, 2019)
Infection with hepatitis B virus (HBV) genotype (GT)-A has been reported to predispose patients to chronic infection. To explore the immune responses in infection with different HBV genotypes and clarify the genotype-dependent pathogenicity, a system mimicking the immune reaction during the early phase of HBV infection is indispensable. To this end, we established a coculture system with the replication-competent HBV molecular clone-transfected HepG2 cells and immortalized human natural killer (NK) cells, NK-92MI. Using this system, we evaluated HBV genotype dependency in NK functions and cell death of HBV positive HepG2 cells induced by NK cells or administration of tumor necrosis factor (TNF) by use of flow cytometry. After coculture with NK cells, we found that GT-A-positive HepG2 cells exhibited lower susceptibility to NK cell-induced cell death than GT-B- or GT-C-positive HepG2 cells. The NK responses of degranulation and cytokine production were not different among transfected HBV genotypes in cocultured cells. The expression levels of death receptors in HBV-transfected HepG2 cells were not different. In GT-A-positive cells, a similar low susceptibility was detected by the external administration of TNF, although relatively higher susceptibility was observed in GT-B- and GT-C-positive cells than in GT-A-positive cells. The activation of caspase signaling was revealed to be responsible for this genotype-dependent susceptibility. In conclusion, our results indicate that the HBV genotype does not influence the NK cell function itself but rather cell vulnerability through the TNF signal pathway. This observation may explain the high chronicity rate of HBV GT-A strains even in adult infections.